A Mathematical Study on Coronavirus Model with Two Infectious States - Lakshmi, V.S.V. Naga Soundarya; Sabarmathi, A. (Journal of Informatics and Mathematical Sciences, 2021)
A SIR model is formulated for COVID-19 with initial and secondary states. Existence and uniqueness of solutions, stability of the model and basic reproduction number were derived. In this article, the vulnerability of COVID-19 in Tirupathur district, Tamilnadu, India is discussed to exhibit the flow of variables of the model using numerical simulations. Also, analysis of recovered is explored for Siddha and allopathy treatments.